Remote Sensing of Planetary Boundary Layer Thermodynamic and Material Structures over a Large Steel Plant, China - Xinbing Ren; Liping Zhao; Yongjing Ma; Junsong Wu; Fentao Zhou; Danjie Jia; Dandan Zhao; Jinyuan Xin (Remote Sensing, 2023)
Air pollutants emitted by industries can significantly affect local air quality and jeopardize human health, and the study of the boundary layer thermodynamic structure and diffusion capacity over industrial plants can be beneficial for the improvement of corporate air pollution control measures. The continuous high temporal and spatial resolution monitoring of the boundary layer structure (thermal, dynamic, and material) by advanced remote sensing instruments over a single strong industrial source (steel plant) in Shanxi Province, China, from May to June 2021 revealed the boundary layer characteristics under the influence of a single strong local anthropogenic influence. Strong nocturnal temperature inversions and grounded temperature inversions were prone to occur over industrial sources. The local wind field was characterized by significant daily variations, with the whole-layer airflow during the daytime dominated by southwesterly winds. At night, under the influence of radiation, topography, and surface, the airflow was dominated by easterly winds with low speeds (less than 2 m/s) in the low altitude range of 100 m, while the wind direction was still dominated by southwesterly winds with higher speeds in the altitude of 100 m. In addition, the average atmospheric diffusion capacity increased significantly with height in the 500 m altitude range, with an increase in rate of about 2~3 times/50 m, and continued to show a discontinuous increasing trend above 500 m. Combined with the wind direction and wind speed contours, it can be seen that the pollutants can be effectively dispersed at a height of 100 m. The thermal and turbulent boundary layer heights were highly consistent, and the material boundary layer height was significantly higher than the thermal and turbulent boundary layer heights during the daytime when convection was strong.